The Role of Religious Figures in Preventing Incest in Tanjung Village: A Maqashid Sharia Perspective - Putri, Tania Kadziyah; Marwa, Muhammad Habibi Miftakhul (Universitas Muhammadiyah Yogyakarta, 2026)
This study examines the phenomenon of incest, a forbidden marriage between closely related individuals, focusing on the case of seven infant deaths in Tanjung Village, Banyumas, resulting from a consanguineous relationship between a father and his biological child. The incidence of incest in Indonesia is notably high. If left unchecked, incest poses a threat to religious teachings and societal resilience. The objective of this research is to conduct an in-depth and critical analysis, using the perspective of maqashid sharia, of the incest phenomenon, its societal impacts, and the role of religious leaders in preventing non-marital incestuous relationships in Tanjung Village, Banyumas Regency. This research is a normative juridical legal study. The data sources used are primary data obtained through field studies and interviews with one figure each from Muhammadiyah, NU, and LDII. Secondary data were obtained through library research of various relevant literature. The collected data were then analyzed using the concept of maqashid sharia. The findings reveal that the role of religious leaders from Muhammadiyah, NU, and LDII in Tanjung Village, Banyumas Regency, is highly strategic in preventing incest. The moral guidance delivered through religious outreach aligns with the objectives of maqashid sharia, preservation of faith, life, intellect, property, and lineage. Incest, whether committed outside or within marriage, contradicts maqashid sharia, as it causes more harm than benefit.